ROC-COPRAS Sebagai Sistem Penunjang Keputusan Kelayakan Penerima Beasiswa Program Indonesia Pintar - Iin, Johar Nur (Jurnal Media Informatika, 2024)
The high dropout rate in Indonesia is one of the government's problems, for which the government is carrying out various efforts, one of which is by providing the Smart Indonesia Program (PIP) Scholarship. The Indonesia Pintar program aims to increase students' opportunities to continue their education at the primary, secondary and higher education levels as a provision to continue into the industrial world. However, not all children can receive PIP assistance with the criteria that have been determined by the government. Budget limitations for the Smart Indonesia Program make it necessary to have a system to support the eligibility of aid recipients. The purpose of this research is to create a decision support system for recipients of the Smart Indonesia Program (PIP) Range Order Centroid (ROC) and Complex Proportional Assessment (COPRAS) methods. This study uses the criteria of father's income, mother's income, father's job, mother's job, distance from home to school, and the number of dependents of parents, means of transportation, and Cumulative Achievement Index (GPA). The results of the research for the decision support system of the ROC-COPRAS method were obtained in the order of alternative ranks, namely A5, A1, A4, A2, and A3, with a utility value (Ui) of 100%. The Decision Support System of the ROC-COPRAS method is expected to be one of the alternative methods in solving multi-criteria decision making problems.